Blood Glucose and Lactate Levels and Cerebral Oxygenation in Preterm and Term Neonates—A Systematic Qualitative Review of the Literature - Mattersberger, Christian; Schmölzer, Georg M.; Urlesberger, Berndt; Pichler, Gerhard (Frontiers in Pediatrics, 2020)
Backgrounds: Cerebral oxygenation monitored non-invasively by near-infrared-spectroscopy (NIRS) is of increasing interest in neonatal care. Cerebral oxygenation is determined by cerebral oxygen delivery and cerebral oxygen consumption. Oxygen delivery as well as oxygen consumption might be influenced by metabolic parameters like blood glucose and lactate. Objective: The aim of the present systematic qualitative review was therefore to identify and summarize all studies, which described cerebral oxygenation measured with NIRS and blood-glucose and/or blood-lactate-levels in neonates. Data sources: A systematic search of Ovid Embase and PubMed was performed. Search terms included: near infrared spectroscopy, fractional tissue oxygen extraction, cerebral tissue oxygen saturation, regional cerebral tissue oxygen saturation, oxygenation, term and preterm neonates, caesarean delivery, transition, after-birth, newborn, vaginal delivery, caesarean delivery, baby, neonatal transition, metabolism, lactate, glucose, blood-glucose-level. Study Selection/Data synthesis: Studies, which analysed cerebral oxygenation and blood-glucose and/or lactate-levels in neonates, were included. Animal studies, duplicates or studies in non-English language were excluded. Results: Twenty-five studies were identified that described blood-glucose and/or lactate levels as primary or secondary outcome parameter with additional measured cerebral oxygenation by NIRS in neonates. 12 studies were included with blood-glucose measurements: four described an association between blood-glucose-levels and cerebral oxygenation two showed no association and six did not report on possible associations. 18 studies were included with lactate measurements: One described an association between lactate-levels and cerebral oxygenation three showed no association and 14 did not report on possible associations. Discussion: The impact of blood-glucose and blood-lactate-levels on the cerebral oxygenation in neonates is still controversial. However, there seems to be an association between cerebral oxygenation and the metabolic parameter blood glucose and lactate, which needs further investigation.